2017
DOI: 10.1038/s41598-017-12574-2
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of the epilepsy gene Depdc5 in mice causes severe embryonic dysmorphology with hyperactivity of mTORC1 signalling

Abstract: DEPDC5 mutations have recently been shown to cause epilepsy in humans. Evidence from in vitro studies has implicated DEPDC5 as a negative regulator of mTORC1 during amino acid insufficiency as part of the GATOR1 complex. To investigate the role of DEPDC5 in vivo we generated a null mouse model using targeted CRISPR mutagenesis. Depdc5 homozygotes display severe phenotypic defects between 12.5-15.5 dpc, including hypotrophy, anaemia, oedema, and cranial dysmorphology as well as blood and lymphatic vascular defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 50 publications
7
41
0
1
Order By: Relevance
“…While the Depdc5 heterozygous animals presented mTORC1 hyperactivation, they did not display any spontaneous seizures,12, 16 suggesting that in these constitutive Depdc5 KO rodent models a functional compensation could partially mask the proepileptic effect of DEPDC5 loss of function. In the acute knockdown experiments presented here the possibility of functional compensation is strongly reduced.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…While the Depdc5 heterozygous animals presented mTORC1 hyperactivation, they did not display any spontaneous seizures,12, 16 suggesting that in these constitutive Depdc5 KO rodent models a functional compensation could partially mask the proepileptic effect of DEPDC5 loss of function. In the acute knockdown experiments presented here the possibility of functional compensation is strongly reduced.…”
Section: Discussionmentioning
confidence: 91%
“…Two other components of the GATOR1 complex, NPRL2 and 3 have been shown to be mutated in familial focal epilepsy with or without focal cortical dysplasia,5, 13, 14, 15 suggesting hyperactivation of mTORC1 as a major cause of epileptic syndromes. Rodent models of Depdc5 confirm the essential role played by this mTOR regulator in development 12, 16. DEPDC5 homozygous null mutations cause embryonic lethality at midgestation due to a range of abnormalities such as general hypoplasia, cranial dysplasia and cardiovascular defects.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The study by Marsan and colleagues showed that mTORC1 is hyperactivated in DEPDC5 knockout mice and that a single prenatal injection of rapamycin could avoid its overall growth delay, demonstrating that embryonic lethality is caused by hyperactivation of mTORC1. Hughes et al (2017) corroborated these findings and reported blood vascular defects, as well as cortical and lymphatic developmental malformations underlying embryonic lethality in DEPDC5 knockout rats …”
Section: Discussionmentioning
confidence: 99%